2013
DOI: 10.1155/2013/412482
|View full text |Cite
|
Sign up to set email alerts
|

Bone Response to Surface-Modified Titanium Implants: Studies on the Early Tissue Response to Implants with Different Surface Characteristics

Abstract: In a series of experimental studies, the bone formation around systematically modified titanium implants is analyzed. In the present study, three different surface modifications were prepared and evaluated. Glow-discharge cleaning and oxidizing resulted in a highly stoichiometric TiO2 surface, while a glow-discharge treatment in nitrogen gas resulted in implants with essentially a surface of titanium nitride, covered with a very thin titanium oxide. Finally, hydrogen peroxide treatment of implants resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…In vitro reports indicate that rough surfaces improve the initial cellular response, including cytoskeletal organization and cellular differentiation with matrix deposition [ 1 3 , 8 , 9 ]. Histologically, it has been demonstrated that rough surfaces can effectively promote better and faster osseointegration, when compared to machined surfaces [ 11 , 12 ]. From a clinical point of view, several studies have reported excellent long-term survival/success rates for rough surface implants [ 5 , 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro reports indicate that rough surfaces improve the initial cellular response, including cytoskeletal organization and cellular differentiation with matrix deposition [ 1 3 , 8 , 9 ]. Histologically, it has been demonstrated that rough surfaces can effectively promote better and faster osseointegration, when compared to machined surfaces [ 11 , 12 ]. From a clinical point of view, several studies have reported excellent long-term survival/success rates for rough surface implants [ 5 , 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another important finding in this study was that bone formation was markedly increased in the rabbit tibia model at approximately 10 days after implant insertion. Previous investigations have indicated that bone formation at 7 days after implant surgery is rare, whereas many studies have reported similar degrees of bone formation between modified Ti surfaces after 14 days (Jimbo et al, ; Kang et al, ; Larsson Wexell et al, ; Yeo et al, ). We anticipated a “burst” in bone formation between 7 and 14 days with regard to bone healing around an implant.…”
Section: Discussionmentioning
confidence: 99%
“…For the clinical application of the Ln2‐P3 treatment, studies with a long follow‐up period are needed. Many rabbit tibia model studies have notably shown no significant histomorphometric differences between modified Ti implant surfaces at >2 weeks after implant insertion (Jimbo et al, ; Larsson Wexell et al, ). The in vivo results of this study also found no significant difference at 11 days after implantation, which were not as clear as the in vitro results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of osseointegration during early healing or local infection may cause bone resorption and lead to treatment failure. Thus, various mechanical, chemical, and physical surface modifications have been performed to improve the bone–implant interaction and biological activity, and some modifications have achieved this result. Plasma‐enhanced chemical vapor deposition (PECVD) is one of these surface modification techniques.…”
Section: Introductionmentioning
confidence: 99%